A comparative study between 0.5% ropivacaine with 50 mcg of dexmedetomidine and 0.5% ropivacaine with 8 mg of dexamethasone for ultrasound-guided supraclavicular brachial plexus block – A randomized controlled study - Narasimhan MK; Renganathan T; Muralidaran S; Rajaram Jayaraman (Asian Journal of Medical Sciences, 2024)
Background: Peripheral nerve block analgesia is augmented using dexamethasone with perineural local anesthesia. Aims and Objectives: The study aimed to assess and compare the effects of dexmedetomidine and dexamethasone on the onset and duration of the sensory and motor block when added to 0.5% ropivacaine for the supraclavicular brachial plexus block. Materials and Methods: This randomized controlled study was conducted at the Department of Orthopedics, Government Stanley Medical College and Hospital, Chennai, for 6 months March 2021–September 2021). Eighty patients were randomly allocated into two groups. Group A (40 patients) received ultrasound-guided supraclavicular brachial plexus block with 0.5% ropivacaine (30 mL)+dexmedetomidine 50 mcg (0.5 mL)+normal saline (1.5 mL). Group B (40 patients) received ultrasound-guided supraclavicular brachial plexus block with 0.5% ropivacaine (30 mL)+dexamethasone 8 mg (2 mL). Results: The dexmedetomidine group had a significantly faster onset of sensory anesthesia (3.9 min) than the dexamethasone group (7.8 min), with a higher duration. The dexmedetomidine group also had a faster onset of motor anesthesia (4.9 min) and a longer duration of analgesia (892.3 min) compared to the dexamethasone group (538 min). The dexmedetomidine group also had a longer duration for rescue analgesia (906 min) than the dexamethasone group (727 min). Visual Analog scores at 10, 14 and 24th h were lower in the dexmedetomidine group than in the dexamethasone group, which is statistically significant (P<0.001). Conclusion: Dexmedetomidine has a faster onset, longer duration, longer analgesia, and prolonged duration for rescue analgesia compared to dexamethasone for ultrasound-guided supraclavicular brachial plexus block, with bradycardia and sedation as side effects.